Mapping and Analysis of Swi5 and Sfr1 Phosphorylation Sites - Sevcovicova, Andrea; Plava, Jana; Gazdarica, Matej; Szabova, Eva; Huraiova, Barbora; Gaplovska-Kysela, Katarina; Cipakova, Ingrid; Cipak, Lubos; Gregan, Juraj (Genes, 2021)
The evolutionarily conserved Swi5-Sfr1 complex plays an important role in homologous recombination, a process crucial for the maintenance of genomic integrity. Here, we purified Schizosaccharomyces pombe Swi5-Sfr1 complex from meiotic cells and analyzed it by mass spectrometry. Our analysis revealed new phosphorylation sites on Swi5 and Sfr1. We found that mutations that prevent phosphorylation of Swi5 and Sfr1 do not impair their function but swi5 and sfr1 mutants encoding phosphomimetic aspartate at the identified phosphorylation sites are only partially functional. We concluded that during meiosis, Swi5 associates with Sfr1 and both Swi5 and Sfr1 proteins are phosphorylated. However, the functional relevance of Swi5 and Sfr1 phosphorylation remains to be determined.
Keywords: Phosphorylation; homologní rekombinace; meiosis; recombination; DNA repair; fosforylace; oprava DNA; Protein Binding; Schizosaccharomyces pombe; Schizosaccharomyces; Homologous Recombination; Meiosis; Schizosaccharomyces pombe - proteiny; Sfr1; DNA Repair; meióza; vazba proteinů; Swi5; phosphorylation; poškození DNA; DNA Damage; Schizosaccharomyces pombe Proteins